Percutaneous fine needle aspiration cytology of the pancreas: advantages and pitfalls. Issue 4 (April 1989) - Kocjan, G; Rode, J; Lees, W R
Abstract : Fine needle aspiration of the pancreas was performed in 62 patients with radiological suspicion of malignancy. All fine needle aspirates were taken under computed tomography or ultrasound guidance. Fine needle aspirates were positive in 31 of 41 patients with histologically or clinically confirmed pancreatic carcinoma. There were no false positive results. The sensitivity of this method for detecting malignant disease was 86%. Cytology was not able to provide conclusive results of benign conditions. Difficulties were encountered in diagnosing well differentiated carcinoma and neuroendocrine tumours and distinguishing them from reactive epithelium and islet cell hyperplasia, respectively. This resulted in a 12.1% false negative rate. There were no complications in our series. Percutaneous fine needle aspiration proved a reliable method of diagnosing pancreatic carcinoma.